Instantaneous modulations in time-varying complex optical potentials - Hayrapetyan, Armen; Klevansky, Sandra Pamela; Götte, Jörg B. (New journal of physics, 2017)
We study the impact of a spatially homogeneous yet non-stationary dielectric permittivity on the dynamical and spectral properties of light. Our choice of potential is motivated by the interest in ##IMG## [http://ej.iop.org/images/1367-2630/19/10/105002/njpaa8245ieqn1.gif] $ \mathcal P \mathcal T $ -symmetric systems as an extension of quantum mechanics. Because we consider a homogeneous and non-stationary medium, ##IMG## [http://ej.iop.org/images/1367-2630/19/10/105002/njpaa8245ieqn2.gif] $ \mathcal P \mathcal T $ symmetry reduces to time-reversal symmetry in the presence of balanced gain and loss. We construct the instantaneous amplitude and angular frequency of waves within the framework of Maxwell’s equations and demonstrate the modulation of light amplification and attenuation associated with the well-defined temporal domains of gain and loss , respectively. Moreover, we predict the splitting of extrema of the angular frequency modulation and demonstrate the associated shrinkage of the modulation period. Our theory can be extended for investigating similar time-dependent effects with matter and acoustic waves in ##IMG## [http://ej.iop.org/images/1367-2630/19/10/105002/njpaa8245ieqn3.gif] $ \mathcal P \mathcal T $ -symmetric structures.
Gesehen am 10.12.2020